Peripheral blood and tissue assessment highlights differential tumor-circulatory gradients of IL2 and MIF with prognostic significance in resectable pancreatic ductal adenocarcinoma - Ahmed, Azaz; Köhler, Sophia; Klotz, Rosa; Giese, Nathalia; Lasitschka, Felix; Hackert, Thilo; Springfeld, Christoph; Zörnig, Inka; Jäger, Dirk; Halama, Niels (OncoImmunology, 2021)
Various reports have pointed out the potential of cytokines as diagnostic and prognostic biomarkers for pancreatic ductal adenocarcinoma (PDA). Nonetheless, the evidence is contradictory and the role of chronic inflammation and relationship between circulatory and corresponding tumoral cytokine levels remain elusive. Utilizing a broad array of cytokines, we identified two opposing parameters: serum levels of interleukin 2 (IL2) and macrophage migration inhibitory factor (MIF) are diagnostic and prognostic factors. While low IL2 levels are associated with PDA, they also relate to a favorable prognosis of patients. In contrast, high MIF levels are associated with PDA and simultaneously related to an unfavorable outcome. MIF levels are associated with the intratumoral density of M2 macrophages (CD163+). Focusing on the tumor-to-serum gradient, we unveiled a different pattern of compartmental cytokine expression between IL2 and MIF. Our findings indicate that an extra-tumoral source of IL2 exists in PDA patients leading to increased detectability in the circulatory system. In case of MIF, the tumor microenvironment is presumably the main site of production and thereby reflected by serum measurements. Taken together, our study describes IL2 and MIF levels as biomarker candidates for diagnosis and prognosis of PDA, highlighting the need for compartmental cytokine analyses. From the perspective of tumor immunobiology, we identify multiple inflammatory states (proposed as types I-III) and see that systemic chronic dysregulation, independent of tumor microenvironment, can be measured and is a possible tool for stratification. Thus, direct correlation of local cytokine levels to peripheral blood levels needs to be regarded with caution.
Gesehen am 09.09.2021